2013
DOI: 10.1097/aog.0b013e3182a6643c
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional Use of Opioids and the Risk of Neural Tube Defects

Abstract: OBJECTIVE Opioid medications are among the most effective analgesics. However, the consequences of opioid exposure to the developing human offspring are not known. We assessed whether maternal opioid use in the periconceptional period was associated with the risk of neural tube defects in the offspring. METHODS We used data from 1998 to 2010 from the Slone Epidemiology Center Birth Defects Study, an ongoing case–control study. Mothers were interviewed by telephone within 6 months of delivery about sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 26 publications
1
103
0
3
Order By: Relevance
“…Considering that opioids have been associated with neural tube defects, cardiac septal defects and the rise in neonatal hospital admissions associated with neonatal abstinence syndrome, our findings raise some concern. [9][10][11][12][13][14] A previous analysis of the overall Canadian population, for the period 2005-2010, showed a similar increase in opioid use of 13.1%. 29 US database studies have also shown increases in opioid use during pregnancy (from the mid-1990s to 2009), but the magnitude of change was generally larger than what we found, with increases in exposure ranging from 0.23-fold to 4.73-fold.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Considering that opioids have been associated with neural tube defects, cardiac septal defects and the rise in neonatal hospital admissions associated with neonatal abstinence syndrome, our findings raise some concern. [9][10][11][12][13][14] A previous analysis of the overall Canadian population, for the period 2005-2010, showed a similar increase in opioid use of 13.1%. 29 US database studies have also shown increases in opioid use during pregnancy (from the mid-1990s to 2009), but the magnitude of change was generally larger than what we found, with increases in exposure ranging from 0.23-fold to 4.73-fold.…”
Section: Discussionmentioning
confidence: 71%
“…5,6,8 Although the effects of opioid use on the developing fetus are poorly understood and findings are varied, associations with complications, including neural tube defects and cardiac septal defects, have been found. [9][10][11] Neonatal abstinence syndrome, a drug-withdrawal syndrome that most commonly occurs after in utero exposure to opioids, has become one of the fastest growing reasons for neonatal hospital admissions. 11,12 Recent studies of opioid exposure in pregnancy have reported incidences of 4.3 to 5.9 cases of neonatal abstinence syndrome per 1000 births.…”
mentioning
confidence: 99%
“…The latter finding contrasts to a Norwegian study [7] based on prospectively ascertained exposure information. A study from the American National Birth Defects Prevention Study [13] found an association between opioid use and a number of specific malformations but the study was retrospective with a possibility of recall bias and also had a high rate of non-responders and has therefore little informative value.…”
Section: Discussionmentioning
confidence: 99%
“…Broussard et al [7] case-control study found that therapeutic maternal opioid treatment within 1 month before and 3 months after conception was significantly associated with some types of congenital heart defects and, at a lower risk, other birth defects. Another study led by Yazdy et al [8] reported an increased risk of neural tube defects. In the other hand, a large population-based cohort study in Norway comparing women who had used codeine during pregnancy with those who had not found no significant association between codeine use and survival, congenital malformation or respiratory depression [9].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 96%